Developmental and genetic factors affecting cardiopulmonary health in children - Bellsham-Revell, Hannah (Henry Stewart Talks, 2025)
Congenital Heart Defects (CHD), Atrial and ventricular septal defect, Atrioventricular septal defect (AVSD), Patent arterial duct, Coarctation of the Aorta (CoA), Tetralogy of Fallot (ToF), Transposition of the great arteries, Genetic syndromes and CHD